Estimating the degree of impact of courses and workshops provided by international organizations for workers in the Northwest Region waste dump (Al-Ekaider) on work from the perspective of workers and their suggestions for developing work: - Bani Hani, Ashraf Saleh Mohammad (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to reveal the degree of impact of courses and workshops provided by international organizations to workers in the Northwest Territory landfill (Al-Ekaider) on work from the point of view of workers and their suggestions for the development of work. Statistical significance (= 0.05) is attributed to the impact of the employee’s work, with a p value of 0.086 and a statistical significance of 0.770. There were no statistically significant differences (p = 0.05) due to the effect of years of experience, as the p value was 0.968 and the statistical significance was 0.329. The results of the study also showed that the highest obstacle is "the incompatibility of the job title with the topics of the courses," with a percentage of 42%. One of the most important recommendations is that the courses are compatible with the job titles.